P0072 C-reactive protein 24 h after colorectal surgery as an early predictor for anastomotic leakage: A preliminary study. (July 2015) - Morandi, E.; Monteleone, M.; Merlini, D.A.; Vignati, G.; D'Aponte, T.; Castoldi, M.
Abstract : Background: Anastomotic leakage represents a serious complication after colorectal surgery for cancer. The early diagnosis of anastomotic leakage is a key point in reducing its clinical consequences. Currently there are no post-surgical markers for early detection of this complication before it becomes clinically apparent. C-reactive protein (CRP) is a biomarker used to help sepsis diagnosing and monitoring antibiotic therapy. The predictive value of CRP as a marker of infective postoperative complications has been widely investigated with promising results. The aim of our study is to evaluate the predictive value of CRP in predicting anastomotic leakage. Methods: A series of 99 consecutive patients, 56 (56.56%) men and 43 (43.43%) women, who underwent elective colorectal surgery for cancer (both laparoscopic and laparotomic with primary anastomosis) were prospectively recruited. Mean age was 68 years. The following data were collected: demographical, surgical, ASA class, and morbidity. 24 h after surgical procedure was completed, the C-reactive protein, leucocytes, and vital signs were evaluated. Findings: 11 (11.11%) patients developed a major anastomotic leak (need for drainage or reoperation). CRP was significantly higher (>12 mg/dL) 24 h after surgery in patients who developed anastomotic leakage, whereas the white blood cell count was not. A CRP cutoff value of 12 mg/dL 24 h after surgery yielded a sensitivity of 80%, a specificity of 95%, and a negative predictive value of 95% for the detection of anastomotic leakage. Interpretation: This is a preliminary study and requires larger sample of patients; however, our results show that increased CRP levels 24 h after colorectal surgery may provide an effective marker to detect anastomotic leakage, before clinical symptoms appear. Moreover, normal CRP values might be also a useful marker to facilitate a safe and early discharge of selected patients after colorectal surgery. CRP is an early, sensitive, and reliable marker of anastomotic leakage.